Nonprofit Organizations from the Perspective of Organizational Development and Their Influence on Professionalization - Katalin Dobrai; Ferenc Farkas (Naše gospodarstvo/Our economy, 2016)
The aim of this paper is to give an overview of the phenomenon of profession- alization that is observable in organizations from the nonprofit sector. Empiri- cal research was conducted among Hungarian nonprofit organizations, and the data were collected within the framework of a country-wide survey. Through the analysis of the research results, the paper provides deeper insights into knowl- edge about professionalization trends in the nonprofit sector. It proves that organizational development positively impacts nonprofit organizations’ improve- ment of their professionalization level and the members of these organizations.